Enhanced understanding of non-axisymmetric intrinsic and controlled field impacts in tokamaks. (24th August 2017) - In, Y.; Park, J.-K.; Jeon, Y.M.; Kim, J.; Park, G.Y.; Ahn, J.-W.; Loarte, A.; Ko, W.H.; Lee, H.H.; Yoo, J.W.; Juhn, J.W.; Yoon, S.W.; et al.
Abstract: An extensive study of intrinsic and controlled non-axisymmetric field ( δ B) impacts in KSTAR has enhanced the understanding about non-axisymmetric field physics and its implications, in particular, on resonant magnetic perturbation (RMP) physics and power threshold ( P th ) for L–H transition. The n   =  1 intrinsic non-axisymmetric field in KSTAR was measured to remain as low as δB / B 0 ~ 4  ×  10 −5 even at high-beta plasmas ( β N ~ 2), which corresponds to approximately 20% below the targeted ITER tolerance level. As for the RMP edge-localized-modes (ELM) control, robust n   =  1 RMP ELM-crash-suppression has been not only sustained for more than ~90 τ E, but also confirmed to be compatible with rotating RMP. An optimal window of radial position of lower X -point (i.e. R x   =   1.44 ± 0.02   m) proved to be quite critical to reach full n   =  1 RMP-driven ELM-crash-suppression, while a constraint of the safety factor could be relaxed ( q 95   =  5 ± 0.25). A more encouraging finding was that even when R x cannot be positioned in the optimal window, another systematic scan in the vicinity of the previously optimal R x allows for a new optimal window with relatively small variations of plasma parameters. Also, we have addressed the importance of optimal phasing (i.e. toroidal phase difference between adjacent rows) for n   =  1 RMP-driven ELM control, consistent with an ideal plasma response modeling which could predict phasing-dependent ELM suppression windows. In support of ITER RMP study, intentionally misaligned RMPs have been found to be quite effective during ELM-mitigation stage in lowering the peaks of divertor heat flux, as well as in broadening the 'wet' areas. Besides, a systematic survey of P th dependence on non-axisymmetric field has revealed the potential limit of the merit of low intrinsic non-axisymmetry. Considering that the ITER RMP coils are composed of 3-rows, just like in KSTAR, further 3D physics study in KSTAR is expected to help us minimize the uncertainties of the ITER RMP coils, as well as establish an optimal 3D configuration for ITER and future reactors.